Plant functional diversity modulates global environmental change effects on grassland productivity. (12th March 2018) - Xu, Zhuwen; Li, Mai‐He; Zimmermann, Niklaus E.; Li, Shao‐Peng; Li, Hui; Ren, Haiyan; Sun, Hao; Han, Xingguo; Jiang, Yong; Jiang, Lin
Abstract: Although much research has explored changes in ecosystem functions associated with global environmental changes, the mechanistic pathways behind the observed changes remain poorly understood. Using an 11‐year experiment that increased growing season precipitation and nitrogen deposition in a temperate steppe, we explored the relative importance of direct and indirect environmental change effects on plant primary productivity. We show that increases in water and nitrogen availability influenced plant productivity via both direct and indirect pathways. While both treatments stimulated plant productivity, changes in plant productivity cannot be explained by observed changes in species or phylogenetic diversity. Instead, the indirect effects of water and nitrogen addition were through their positive effects on plant functional diversity. Importantly, while the increase in one component of functional diversity (community‐level weighted mean of plant stature) resulted in increased productivity, the increase in another component of functional diversity (functional dispersion) resulted in decreased productivity. Synthesis . Our study provides the first evidence for the opposite effects of community‐weighted means and functional dispersion of plant functional traits on grassland productivity and highlights the importance of both traits of dominant species and trait distribution among species in modulating the effects of global changes on ecosystem functions. Abstract : Our study provides the first evidence for the opposite effects of community‐weighted means and functional dispersion of plant functional traits on grassland productivity and highlights the importance of both traits of dominant species and trait distribution among species in modulating the effects of global changes on ecosystem functions.